Intelligent Data Catalogs Using Metadata Automation: Architectures, Standards, and Scalable Frameworks for Modern Data Ecosystems - Srinivasa Rao Seetala (International Journal of Scientific Research in Science and Technology, 2024)
Modern enterprises generate vast volumes of structured and unstructured data across distributed environments, including cloud platforms, on-premises systems, IoT streams, and data lakes, creating significant challenges in organizing, accessing, and governing these assets effectively. Traditional data management approaches, which rely heavily on manual documentation, siloed repositories, and static metadata definitions, struggle to ensure discoverability, governance, data quality, and usability at scale, often leading to data redundancy, inconsistency, and limited trust in analytics outcomes. In response to these challenges, intelligent data catalogs powered by automated metadata ingestion, enrichment, and classification have emerged as a critical solution for enabling efficient data discovery, end-to-end lineage tracking, regulatory compliance, and collaborative data usage across organizations. These systems leverage advanced techniques such as machine learning, semantic modeling, and knowledge graphs to transform metadata into a dynamic, context-aware asset that supports real-time insights and decision-making. This paper explores the evolution of metadata systems from early foundational frameworks in the 2000s, which emphasized standardization and interoperability, to modern intelligent data catalog platforms developed prior to 2024 that integrate automation, scalability, and semantic intelligence. It highlights key architectural models, metadata lifecycle automation techniques, and distributed system considerations, while synthesizing insights from established metadata standards, academic literature on data catalogs, and large-scale metadata management systems to propose a comprehensive, scalable framework for building intelligent, metadata-driven ecosystems that enhance data accessibility, governance, and enterprise innovation.
Keywords: Data Catalog; Metadata Automation; Data Governance; Metadata Management; Data Discovery; Data Lineage; Knowledge Graphs; Data Lakes; DCAT; Semantic Metadata